Monitoring the progress of health-related sustainable development goals (SDGs) in Brazilian states using the Global Burden of Disease indicators - Machado, Daiane Borges (2020)
Center of Data and Knowledge Integration for Health. Oswaldo Cruz Foundation. Salvador, BA, Brazil/Centre for Global Mental Health. LondonSchool of Hygiene & Tropical Medicine. London, UK.